Relationship Between Parenting Patterns and Foot Intake with The Nutritional Status of The Toddlers in Tena Teke Community Health Center - Veronika Bili Bili; Marselinus Laga Nur; Yoseph Kenjam (Universitas Nusa Cendana, 2022)
Nutritional problems in children under five are still a major public health problem, especially in Indonesia. Toddlers who are malnourished in Southwest Sumba Regency in 2017 amounted to 907 cases(9,4 %); in 2018 increased to 939 cases(9,8 %)and in 2019 decreased to 348 cases(4,2%). At the Tena Teke Community Health Center, with the nutritional status of toddlers, there were 53 cases, increasing to 55 cases in 2018 and 2019, decreasing to 36 cases. The decline is known to prevent cases of malnutrition, but the figure is still quite high. This study aimed to analyze the relationship between parenting patterns and food intake with the nutritional status of children under five in the working area of ​​the Tena Teke Health Center. This type of research used analytical survey research methods. The research design used was a case-control study. Case samples were 37 people, and control samples were 37 people. The results showed that all the variables studied, namely feeding practices (OR = 34,105), personal hygiene practices (OR = 11,963), food preparation and storage (OR = 6,286), energy intake (0R= 0,221), and protein intake (OR= 17,188) associated with the nutritional status of toddlers. Toddlers' mothers should regularly attend Posyandu and actively seek information related to toddler growth. Keywords: food intake, nutritional status, toddler